Cardiovascular events and all‐cause mortality in patients with chronic obstructive pulmonary disease using olodaterol and other long‐acting beta2‐agonists. Issue 8 (13th May 2022) - Rebordosa, Cristina; Farkas, Dóra Körmendiné; Montonen, Jukka; Laugesen, Kristina; Voss, Florian; Aguado, Jaume; Bothner, Ulrich; Rothman, Kenneth J.; Zint, Kristina; Mines, Daniel; Ehrenstein, Vera
Abstract: Purpose: We examined the effect of olodaterol on the risk of myocardial ischaemia, cardiac arrhythmia, and all‐cause mortality compared with use of other long‐acting beta2‐agonists (LABAs). Channelling bias was also explored. Methods: This Danish population‐based cohort study used data linked from registries of hospital diagnoses, outpatient dispensings, and deaths. It included patients (aged ≥40 years) with a diagnosis of chronic obstructive pulmonary disease (COPD) who initiated olodaterol or another LABA. Using matching and propensity score (PS) stratification, we calculated adjusted incidence rate ratios (IRRs) using Poisson regression, followed by several additional analyses to evaluate and control channelling bias. Results: The IRRs of cardiac arrhythmias or myocardial ischaemia among users of olodaterol ( n  = 14 239) compared to users of other LABAs ( n  = 51 167) ranged from 0.96 to 1.65 in various analyses, although some estimates had low precision. Initial analysis suggested an increased risk for death with olodaterol compared with other LABAs (IRR, 1.63; 95% CI, 1.44–1.84). Because olodaterol prescribing was associated with COPD severity, the mortality association was attenuated by using different methods of tighter confounding control: the IRRs were 1.26 (95% CI, 0.97–1.64) among LABA‐naïve LABA/LAMA users without recent COPD hospitalisation; 1.27 (95% CI, 1.03–1.57) in a population with additional trimming from the tails of the PS distribution; and 1.32 (95% CI, 1.19–1.48) after applying overlap‐weights analysis. Conclusions: Olodaterol users had a similar risk for cardiac arrhythmias or myocardial ischaemia as other LABA users. The observed excess all‐cause mortality associated with olodaterol use could be due to uncontrolled channelling bias.